Analysis of the Implementation of the INA-CBGs System Using the Hot-Fit Method in Outpatient Dr. M. Djamil Padang in 2019 - Devid Leonard; Oktamianiza Oktamianiza; Linda Handayuni; Rahmawita Rahmawita (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
The INA-CBGs system in Dr. M. Djamil Padang still has several obstacles and problems related to its implementation. The purpose of this study was to analyze the implementation of the INA-CBGs system using the HOT-FIT method in outpatient Dr. M. Djamil Padang. This research was conducted at Dr. M. Djamil Padang on 20 to 26 June 2019. This type of research uses a qualitative descriptive method with a case study approach. The research informants were the Head of Medical Records, the Medical Records officer in the coding section, the Casemix officer, and the SIMRS officer. The data collection technique is in-depth interviews. Analysis in data processing, namely transcription, reduction, coding, categorization, and themes. The results of this study found that in the implementation of the INA-CBGs system there were still some problems where the system often experienced errors where data did not appear in the software, frequent network disruptions, lack of compliance of officers in data entry and data entry, and no training. The conclusion is the lack of cooperation of officers in filling and inputting patient data, lack of training and socialization related to the importance of completeness of data for the grouping process, SPO applied from the hospital does not exist because there is an SPO implemented by the government, and SIMRS officers must improve system quality and quality. network so that the implementation of the INA-CBGs system runs smoothly. Keywords: implementasion of the INA-CBGs system; Hot-Fit ABSTRAK Sistem INA-CBGs di RSUP Dr. M. Djamil Padang masih terdapat beberapa kendala dan permasalahan terkait pelaksanaannya. Tujuan dari penelitian ini adalah menganalisis pelaksanaan Sistem INA-CBGs Menggunakan Metode HOT-FIT di Rawat Jalan RSUP Dr. M. Djamil Padang. Penelitian ini dilakukan di RSUP Dr. M. Djamil Padang pada 20 s/d 26 Juni 2019. Jenis penelitian menggunakan metode deskriptif kualitatif dengan pendekatan case study. Informan penelitian yaitu Kepala Rekam Medis, petugas Rekam Medis bagian koding, petugas Casemix, dan petugas SIMRS. Teknik pengumpulan data yaitu wawancara mendalam. Analisis dalam pengolahan data yaitu transkripsi, reduksi, koding, kategorisasi, dan tema. Hasil penelitian ini menemukan bahwa dalam pelaksanaan sistem INA-CBGs masih ditemukan beberapa kendala dimana sistem sering mengalami error yang manadata tidak muncul pada software, sering terjadi gangguan jaringan, kurangnya kepatuhan petugas dalam pengisian dan penginputan data, tidak adanya pelatihan. Kesimpulan yaitu kurangnya kerjasama petugas dalam pengisian dan penginputan data pasien, kurangnya pelatihan dan sosialisasi terkait pentingnya kelengkapan data untuk proses grouping, SPO yang diterapkan dari rumah sakit tidak ada karena ada SPO yang diterapkan oleh pemerintah, serta petugas SIMRS harus meningkatkan lagi kualitas sistem dan kualitas jaringan agar pelaksanaan sistem INA-CBGs berjalan lancar. Kata kunci: implementasi sistem INA-CBGs; Hot-Fit